Birth weights of infants of first generation Asian women in Britain compared with second generation Asian women. - Dhawan, S. (BMJ Group, 1995)
OBJECTIVES--To compare birth weights of infants of first generation Asian women (women born in the Indian subcontinent) with those of infants of second generation Asian women (born in the United Kingdom). DESIGN--Retrospective case note study. SETTING--Bolton District General Hospital. SUBJECTS--331 Asian women who gave birth between January 1989 and December 1989: 220 of these women were first generation Asians and 111 were second generation Asians. MAIN OUTCOME MEASURE--Birth weights of babies born to first and second generation Asian women. RESULTS--At all gestational ages at delivery, babies born to second generation Asian women were heavier than those born to first generation women. The mean birth weight for babies of second generation women was 3196 g, 249 g more than the mean birth weight of 2946 g of babies of first generation women (P < 0.001). After a stepwise multiple regression analysis was carried out the adjusted difference in birth weights was 280 g, greater than the crude difference. CONCLUSION--Birth weights are important in relation to perinatal mortality, which is notoriously high among Asians. The results of this study indicate that there is hope for lowering of perinatal mortality and improving postnatal growth in babies of second generation Asians.